Generation of G-Code on aluminum blocks using vertical CNC machine / Nur Adriana Auni Mohd Andrie - Mohd Andrie, Nur Adriana Auni (2022)
The Final Year (FYP) is called generation of G-Code on Aluminium Blocks using CNC Milling Machine. In computer-aided design and manufacturing (CAD/CAM), it is basically the language for computer numerical control (CNC). G-code is a metric-based numeric control system for CAM-controlled devices like CNC milling machines. Software such as SURFCAM can be used to generate the code. If using the conventional machining there will always be some differences and inconsistencies of the machined part. The aim of this study is to be able to generate G-Code of a design on aluminium blocks using vertical CNC milling machine and fabricate the machined part. After that, it will be preciselydrawn in the software. When doing the machining process in the software, a warning is always displayed. It shows that if any imperfections occur, everything is solved perfectly in order to obtain good results. As a nutshell, after the machining process is complete, the software can generate the code automatically and it will come out beautifully. It provides the G-Code generation as well as an example of how it is used in actual programming code. To conclude this Final Year project (FYP), this project can surely help to master the generation of g-code using aluminium blocks using vertical CNC machine.